Labour Law – Employees Provident Fund Board v. M.A. Ally & Co. Ltd. - Nijar, Gurdial Singh (Journal of Malaysian and Comparative Law, 2018)
Labour Law – Employees Provident Fund Board v. M.A. Ally & Co. Ltd.